The hidden potential of archaea in carbon and nitrogen cycling in agricultural soils: a review - Speek, Brenda M.; Suleiman, Afnan Khalil Ahmad; Keuning, Eline; Sechi, Valentina; Buisman, Cees J. N.; Bezemer, T. Martijn (Frontiers in Microbiology, 2026)
The soil microbiome drives soil nutrient cycling and is intrinsically linked to plant productivity in agriculture. Archaea are members of many soil microbiomes and play important roles in nutrient cycling, particularly in the carbon and nitrogen cycle. Many archaeal groups contribute to both carbon and nitrogen cycles, but their dual roles are often underappreciated. For instance, ammonia-oxidizing archaea couple ammonia oxidation to carbon fixation, contributing to carbon sequestration in soils. Methanogenic archaea use ATP produced through methanogenesis for nitrogen fixation. N-DAMO archaea directly couple carbon and nitrogen cycling through nitrate-dependent anaerobic methane oxidation, while haloarchaea contribute to carbon sequestration and denitrification. Here, we synthesize the latest research regarding the dual roles of archaea in carbon and nitrogen cycling in agricultural soils. We pay special attention to how nutrient input influences these roles. We show that the relevance of the processes is highly context dependent. In addition, we identify several research directions that will help harness the difference roles of archaea in carbon and nitrogen cycling to increase agricultural productivity and sustainability. Finally, we showcase that abundance and activity of archaea in the soil microbiome could be steered through nutrient input or microbiome engineering strategies.